Ավետիք Իսահակյանի անձնական գրադարանը Երևանում - Առաքելյան, Նունե (Հայաստանի ազգային գրադարան)
The book has been a sacred object for Avetiq Isahakyan and the personal library of that writer appears to be the real proof of it. Avetiq Isahakyan’s private library is the specific mirror of his life, which reflects the writer’s nature, his interests and preferences. The library is the perceptible part of Varpet’s rich heritage, which must be kept and transmited to the next generations.
Keywords: Գրադարաններ; Մշակութային ժառանգություն